Application of paraconsistent logic to support the decision on the return of face-to-face academic activities at the university after Covid-19 (Research, Society and Development, 2022)
During the Covid-19 pandemic peak period, changes were devised for society to adapt to the new lifestyle without affecting its development. Among others, education was one of the most affected areas in this period due to the mandatory social distancing. Education institutions adapted to this new scenario by switching from face-to-face to remote teaching, which brings advantages and disadvantages. To better understand this new teaching-learning pedagogical approach, it is important to listen to those intimately connected in this process: professors and students. Since they provide personal and subjective opinions connected to their own cultures, perceptions, and other very personal variables, assessing their opinions requires a different approach based on unusual logics, in which the paraconsistent logic appears as a potential tool. This research aims to apply the paraconsistent annotated evidential logic Eτ (PAEL) in the opinion of students and professors of an engineering post-graduate program in the state of São Paulo to evaluate whether or not to return to face-to-face academic activities at the university, after the Covid-19 pandemic. A survey was applied to a sample of professors and students, embracing nine variables related to teaching, research, economics, time, and efficiency. Results show that, although research and time indicators are located within the ‘truth’ region of the cartesian unitary square, the barycenter is in the 'almost true' region, indicating an inconclusive response as to whether or not to return to face-to-face academic activities. This study contributes to discussions about the newly imposed after Covid-19-scenario towards more effective pedagogical approaches.